Topical application of moringa leaf extract gel (Moringa oleifera Lam.) on the number of fibroblasts in the healing of stomatitis in male Wistar rats (Rattus norvegicus): Aplikasi topikal gel ekstrak daun kelor (Moringa oleifera Lam.) terhadap jumlah fibroblas dalam penyembuhan stomatitis pada tikus putih galur wistar jantan (Rattus norvegicus) - Putu Yetty Nugraha; Putu Ayu Mas Avriella Rachmadianthi Putri (Makassar Dental Journal, 2026)
Moringa leaves (Moringa oleifera Lam.) are widely used for healing and nutrition because they contain tannins, flavonoids, and saponins. Flavonoids can acce- lerate the healing of inflammation by increasing fibroblasts. This article explores the effect of topical application of ML extract gel on increasing the number of fibroblasts in the healing process of stomatitis in male Wistar rats. This laboratory experimental study used a randomised post-test only control group design. Thirty rats were divided into five groups: positive control (K+), negative control (K-), and ML extract gel concentrations of 15% (P1), 20% (P2), and 25% (P3). Stomatitis was induced using 35% hydrogen peroxide for 6 days, then the gel was applied to the stomatitis for 3 days. The number of fibroblasts was observed on day 4 using HE staining, showing that the average number of fibroblasts in (K-) was 3.33, (K+) was 8.16; P1 was 5.00, increased to 6.50 in P2, and re-ached 7.33 in P3. Statistical tests showed a significant difference (p<0.05) between the treatment group and the negative control. It was concluded that the application of 25% DK extract gel had higher efficacy than other concentrations.